Les singularités de la version copte des Actes de Pilate - Dubois, Jean-Daniel 1946-; Roquet, Gérard (2011)
The Coptic version of the Acta Pilati was translated from a now lost Greek text, quite early in the history of the transmission of the text. It preceeds all known Greek manuscripts by several centuries. It is therefore important to examine a series of variant readings of the Coptic version, especially when these variants are also attested by other manuscripts.
Keywords: Pilatusakten; Koptisch